2019
DOI: 10.1007/s13361-019-02147-0
|View full text |Cite
|
Sign up to set email alerts
|

Capillary Vibrating Sharp-Edge Spray Ionization (cVSSI) for Voltage-Free Liquid Chromatography-Mass Spectrometry

Abstract: Here we report a continuous flow-based ionization method, capillary Vibrating Sharp-edge Spray Ionization (cVSSI), that nebulizes liquid sample directly at the outlet of a capillary without using high-speed nebulization gas or a high electrical field. cVSSI is built upon the recently reported VSSI principle which nebulizes bulk liquid using vibrating sharp-edges. By attaching a short piece of fused silica capillary on top of the vibrating glass slide in VSSI, liquid is nebulized at the outlet of the capillary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 35 publications
1
58
0
Order By: Relevance
“…Finally, we tested the quantification capability of the present workflow. As reported in our previous studies, 33,36 VSSI offers good linear ranges for direct spray of analytes. Here, we first confirmed that a linear range from 1 nM to 10 μM can be achieved for clarithromycin in water (Figure S4).…”
Section: Characterization Of Quantification Performance In Pbs and Se...supporting
confidence: 66%
“…Finally, we tested the quantification capability of the present workflow. As reported in our previous studies, 33,36 VSSI offers good linear ranges for direct spray of analytes. Here, we first confirmed that a linear range from 1 nM to 10 μM can be achieved for clarithromycin in water (Figure S4).…”
Section: Characterization Of Quantification Performance In Pbs and Se...supporting
confidence: 66%
“…Therefore, no conclusions can be drawn with regard to the degree of membrane‐induced oligomerization. To disentangle the routes of formation for such a heterogenous mixture of oligomeric species is the subject of future, more extensive experiments employing a greater number of lipid systems as well as gas‐phase separations and reactivity studies . This process will also be examined by MD simulations where multiple peptides are examined with the membrane systems.…”
Section: Resultsmentioning
confidence: 99%
“…Here we report a simple instrumentation method that can effectively suppress corona discharge for aqueous solutions based on capillary vibrating sharp-edge spray ionization (cVSSI). cVSSI is a process that can generate a plume of liquid droplets at the outlet of a capillary by simply attaching it to a vibrating glass slide. , By combining the cVSSI process with a bias voltage, negative ion signals of various analytes including DNA, proteins, peptides, and oligosaccharides from aqueous solutions are improved significantly. While several ultrasonic nebulization systems that can be coupled with ESI have been developed including an array of micromachined ultrasonic electrospray (AMUSE), ultrasonically assisted electrospray, single pulse nanoelectrospray, the capability of suppressing corona discharge for these methods has not been reported.…”
mentioning
confidence: 99%